العنف الأسري في مملكة البحرين ودور المؤسسات الأهلية والقضاء الشرعي في معالجته : دراسات فقهية تحليلية - عبد الله، سلمان محسن (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research explains the concept of domestic violence in the Kingdom of Bahrain, its types, and its causes in the light of Islamic jurisprudence. It studies also the reality of domestic violence in Bahraini society and its implications and it highlights the position of Islamic law on it. The research explains the role of civil institutions and the legal judiciary in addressing domestic violence in the Kingdom Bahrain in the light of Islamic jurisprudence. The researcher also referred to the findings, suggestions and recommendations that will enrich the topic in scientific and practical terms. The researcher has used the descriptive approach to study the basic concepts constituting the elements of the research, through discussing the sayings of the Muslim scholars on the issue of domestic violence in terms of jurisprudence. He has also used the analytical method to analyse and discuss the opinions of jurists, present legal texts and their relationship to this topic, and to inquire about domestic violence issues with civil institutions and the legal judiciary as much as possible in the Kingdom of Bahrain.The researcher also conducted a field study through an open interview to obtain possible data on domestic violence In the Kingdom of Bahrain with officials in the relevant civil institutions and the legal judiciary to obtain information related to domestic violence, which will contribute to the scientific analysis of the problem and enrich the research with important information, which requires serious study and scientific research to explain its causes and effects and offers its treatment to reduce it in light of Islamic law.